Frustrated Interfaces Facilitate Dynamic Interactions between Native Client Proteins and Holdase Chaperones. (17th September 2019) - He, Lichun; Hiller, Sebastian
Abstract: Molecular chaperones are crucial for cellular life to ensure that all proteins obtain their right fold and functionality. Many chaperones promiscuously bind a wide spectrum of client proteins, ranging from nascent to quasi‐native and native proteins. Several recent studies have investigated, at atomic resolution, how chaperones interact with native proteins. Native proteins feature a wide variety of structural conformations, and therefore, a given chaperone cannot accomplish full surface complementarity to all of its client proteins. This limitation is circumvented by the recognition of frustrated regions on the client protein surface by the chaperone. In this interaction mode, the chaperone forms a multitude of transient local interactions with some segments of the client, whereas other parts are transiently not in favorable interactions. A permanent rearrangement of the client conformation on the chaperone occurs. Reconfiguration on the chaperone surface also gives the client a chance to fold into its correct, minimally frustrated conformation. Abstract : Folding native : Chaperones bind native client proteins on locally frustrated surfaces in a multiconformational ensemble. The ensemble of client structures interconverts under thermal equilibrium, while the client remains bound to the chaperone. The energy landscape of this interaction mode is broad and the large conformational entropy of the bound state adds favorably to the free energy of binding.